HVAC Systems Design Hand book - Haines, Roger W. (McGraw-Hill, 2003)
"Thoroughly updated with the latest codes, technologies, and practices, this all-in-one resource provides details, calculations, and specifications for designing efficient and effective residential, commercial, and industrial HVAC systems." "HVAC Systems Design Handbook, Fifth Edition, features new information on energy conservation and computer usage for design and control, as well as the most recent International Code Council (ICC) Mechanical Code requirements. Detailed illustrations, tables, and essential HVAC equations are also included. This comprehensive guide contains everything you need to design, operate, and maintain peak-performing HVAC systems."--BOOK JACKET.